Environmental Kuznets Curve Hypothesis With Considering Ecological Footprint and Governance Quality: Evidence From Emerging Countries - Mahmoodi, Majid; Dahmardeh, Nazar (Frontiers in Environmental Science, 2022)
Improving the environmental quality and economic growth simultaneously, and examining the variables affecting this nexus, has been one of the most important issues for researchers and policymakers in recent years, especially following the United Nations 2030 Agenda Sustainable Development Goals. The aim of this study is to investigate the nexus among the ecological footprint as a multi-aspect indicator of environmental degradation, economic growth, renewable and non-renewable energies, and governance quality within the Environmental Kuznets Curve (EKC) hypothesis framework for two panels of European and Asian emerging countries during 1996-2017. For this purpose, we employ second-generation panel techniques that consider cross-sectional dependency in panel data. Augmented Mean Group estimation results indicate an inverted U-shape nexus among the economic growth and ecological footprint, which implies validation of the EKC hypothesis in all two panels of countries. The findings indicate the positive impact of non-renewable energy and the negative influence of governance quality on the ecological footprint in all two panels. While, there is evidence of the negative impact of renewable energy on ecological footprint only in European emerging countries. In summary, the findings recommend that governments and policymakers pay closer attention to implementing non-renewable energy restrictive policies and renewable energy incentive policies. Furthermore, this is important to plan for improving various dimensions of governance quality in order to achieve better adoption and implementation of environmental policies, especially in the Asian emerging countries it can lead to a more positive impact on environmental quality according to the results of estimated coefficients.